INOVASI TEKNOLOGI SURYA GENERASI BARU UNTUK KONVERI ENERGI, INTEGRASI TERMAL, PENGERINGAN, DESALINASI, DAN BANGUNAN CERDAS - Sarinah Pakpahan; Fuad Pontoiyo; Jamal Darusalam Giu (Journal Of Renewable Energy Engineering, 2026)
This article presents a comprehensive Systematic Literature Review (SLR) of cutting-edge advancements in solar energy technology, mapping the paradigm shift from single-component efficiency to multi-functional system integration. Utilizing a data corpus from JREE and PLTS comprising high-repute publications from the 2023–2026 period, this study identifies five primary innovation clusters: (1) optimization of photovoltaic (PV) systems and perovskite solar cells; (2) integration of thermal energy storage utilizing Phase Change Materials (PCM); (3) hybrid solar drying applications for the agro-industrial sector; (4) desalination technologies based on interfacial evaporation; and (5) smart building implementation via data-driven control systems. In response to critical reviews, this article strengthens its methodological foundation by providing technical justification for selecting the data corpus, ensuring it is representative of global trends, and mitigating the limitations of abstract-based analysis through an in-depth examination of key studies. Specific focus is placed on the role of Artificial Intelligence (AI), as this review transitions from a descriptive narrative to a systematic analysis of the requirements for interpretable and robust models in system monitoring. The analytical results indicate that the synergy between advanced materials such as nanofluids and metamaterials—and multi-objective optimization algorithms is pivotal to achieving decarbonization targets. Overall, this review provides a roadmap for researchers in developing solar systems that are not only technically efficient but also economically viable and sustainable, supported by a comprehensive reference list that reinforces the reliability of this data synthesis.